Management of steep land - Verma, G P; Singh, Y P; Singh, Anil Kumar (Indian Farming, 2018)
Steep land is classed as unsuitablefor arable farming under the LandCapability Classification, as it usuallyhas shallow soil severely eroded byrainwater, impoverished of plantnutrientsand soil colloids. Still suchland is brought under the plougheven in advanced countries likeU.S.A. and Canada. But no intensiveresearch on management of such landhas been conducted and consequentlyfool proof technology for appropriatemanagement of steep land is notavailable. Hence, the need forintensive research on steep landmanagement cannot be overemphasized. Various aspects to becovered are: land and watermanagement practices, nature anddensity of vegetative cover,negotiation of slope, run-offcollection and recycling and alternateland-use systems.